A Review of Newborn Screening for VLCADD: The Wisconsin Experience - Breanna Mitchell; Jessica Scott-Schwoerer; Ashley Kuhl; Kristina Garcia; Patrice Held (International Journal of Neonatal Screening)
Very-long-chain acyl-CoA dehydrogenase deficiency (VLCADD) is due to a defect in metabolism of long-chain fatty acids. Infants with VLCADD may experience cardiomyopathy, hypoglycemia, or even death; thus, early detection and intervention is crucial. The spectrum of disease and natural variation in newborn metabolism, however, lead to overlap in acylcarnitine values between affected and unaffected individuals, which contributes to the difficulty in identifying true positive cases while minimizing false positive cases. VLCADD was added to the state of Wisconsin’s newborn screening (NBS) panel in 2000. A previous retrospective review of VLCADD screen positive cases identified between 2000 and 2014 resulted in a change to the screening algorithm. Following implementation, a reduction in the percentage of false positive screens from 25.3% to 20.4% was observed between 2015 and 2021. The overall PPV also decreased, from 37.2% to 28%, due to an increase in the number of carriers identified (27.5% of cases in 2000–2014 and 51.8% of cases in 2015–2021). A data review also identified three long-chain acylcarnitine elevations (C14:1, C14:1/C16, and C14:1/C2) that had statistically significant differences in concentrations in true positive populations versus false positive populations. Utilization of the C14:1, C14:1/C16, and C14:1/C2 values in newborn screening may provide clearer distinction between true positive and carrier populations and additionally increase the PPV of this screen.